A study on the effect of csr activities on customer loyalty: the case of shinhan bank’s in Vietnam = Ảnh hưởng của trách nhiệm xã hội doanh nghiệp đến lòng trung thành của khách hàng. Nghiên cứu điển hình tại ngân hàng Shinhan Bank Việt Nam - Cho, Kwang Mae (2020)
In order to reach the above-mentioned aims, the research focuses on the following main objects: - Presents the need for this study, the purpose of the study, the method of research, and the scope of research; - Explained the rationale behind the company's social responsibility and explained, for example, the corporate social responsibility activities of Shinhan Bank.; - Established research models and hypotheses based on theoretical and prior studies, and the design of the empirical investigation provided operational definitions of variables and specific measurement questions for each variable. - We conducted an empirical survey and analysis to verify the hypothesis of this time. - The results of the study were summarized, the limitations of the research, and the direction of future research. - Factors of Vietnam business environments that impact the operation of FDI firms from South Korea.